Financial education, an approach to social growth and development - Jay Vanegas, Witt; Mugno Noriega, Ana; Luis López, José; Jay Vanegas, Witt; Mugno Noriega, Ana; Luis López, José (Corporación Universitaria Americana, 2021)
The objective of this article was to demonstrate, throughinternational and national experiences, the differentfinancial skills of people, in order to build a foundation thatwill serve as the necessary tools for an effective educationof the Colombian population. The methodology used inthe development of this study is quantitative, descriptiveand documentary design, using the summary source ofthe work of specialization Financial Education as anAlternative to Improve the Quality of Life of the Societyand hermeneutics as a technique of interpretation of thetexts. The conclusion after analyzing all the antecedentsand theoretical foundations regarding the topic ofFinancial Education with respect, and analyzing thedifferent contexts in which this topic has been acquiringimportance, it can be concluded that financial educationplays an important role in the development of the society,at the moment in which States create strategies andpolicies related to the subject, conditioned to their contextand taking into account the needs of their the needs oftheir population, the results have been positive.